2016
DOI: 10.1002/path.4853
|View full text |Cite
|
Sign up to set email alerts
|

Lung neuroendocrine tumours: deep sequencing of the four World Health Organization histotypes reveals chromatin‐remodelling genes as major players and a prognostic role for TERT, RB1, MEN1 and KMT2D

Abstract: Next‐generation sequencing (NGS) was applied to 148 lung neuroendocrine tumours (LNETs) comprising the four World Health Organization classification categories: 53 typical carcinoid (TCs), 35 atypical carcinoid (ACs), 27 large‐cell neuroendocrine carcinomas, and 33 small‐cell lung carcinomas. A discovery screen was conducted on 46 samples by the use of whole‐exome sequencing and high‐coverage targeted sequencing of 418 genes. Eighty‐eight recurrently mutated genes from both the discovery screen and current lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
191
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 190 publications
(208 citation statements)
references
References 40 publications
12
191
1
Order By: Relevance
“…Regarding SCLC in particular, homozygous deletions comprised 39.4% of the cases. Moreover, when loss of heterozygosity was also included, the RB1 alterations prevailed among SCLC cases, at 91% (22). Loss of TP53 was also frequent among highgrade NETs, as it was detected in 48.5% of SCLC and 40.7% of LCNEC cases, whereas fewer than one-third of carcinoids presented with TP53 losses.…”
Section: Cell-cycle Regulatory Genesmentioning
confidence: 98%
See 4 more Smart Citations
“…Regarding SCLC in particular, homozygous deletions comprised 39.4% of the cases. Moreover, when loss of heterozygosity was also included, the RB1 alterations prevailed among SCLC cases, at 91% (22). Loss of TP53 was also frequent among highgrade NETs, as it was detected in 48.5% of SCLC and 40.7% of LCNEC cases, whereas fewer than one-third of carcinoids presented with TP53 losses.…”
Section: Cell-cycle Regulatory Genesmentioning
confidence: 98%
“…Simbolo et al showed that chromatin-remodeling genes were mutated in carcinoids (45.5%) and carcinomas (55.0%) at similar rates (22). Specifically, the histone-lysine N-methyltransferase 2 (KMT2) family of covalent histone modifiers (KMT2A, KMT2C and KMT2D) was mutated in 13.6% carcinoids versus 26.7% carcinomas and the AT-rich interaction domain (ARID) family, involved in the switch/sucrose nonfermentable (SWI-SNF) complex (ARID1A, ARID1B, and ARID2), had mutations in 9.0% carcinoids versus 10.0% carcinomas (22).…”
Section: Chromatin-remodelling Genesmentioning
confidence: 99%
See 3 more Smart Citations